Subsidiarity and Economic Reform in Europe - Gelauff, George (Springer, 2017)
Subsidiarity in the European Union, as the guiding principle of decision-making "close to the people", is often motivated and discussed from a predominantly political perspective. In this book, twenty-five renowned economic researchers and policy experts draw the demarcation between national and European policies from an economic viewpoint. Insights from economic theory and empirical research are used both to analyse the assignment of policies between the EU and its Member States and to identify appropriate levels of decision-making. Four key areas of the renewed Lisbon strategy are highlighted for their policy relevance: education and innovation, the internal market, corporate taxation, and regional and transport policy.